Classroom Situation in Reading Classes of the Foundation English Course (FEC) at International Islamic University Chittagong (IIUC): An Empirical Study (IIUC Studies, 2012)
The article aims at depicting the present scenario of teaching reading skill to the students of Foundation English Course (FEC) through an empirical study. Two questionnaires have been used for collecting data from learners and teachers to point out the weak areas of ineffective teaching and to identify the shortcomings in teaching reading skill. Collected data have been analyzed under eight points and recommendations have been made separately under those points to overcome the weak areas of ineffective teaching.DOI: http://dx.doi.org/10.3329/iiucs.v6i0.12246IIUC Studies Vol.6 2010: 7-34